Promosi Kesehatan Tentang Pencegahan Infeksi Saluran Pernapasan Akut di Kelurahan Randu - Dyah Restuning Prihati; Maulidta Karunianingtyas Wirawati; Catur Asih Lestari; Edi Wibowo; Itsnaeni Khotimah; Kusdino Kusdino; Rina Fajariyati (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
Acute Respiratory Tract Infection (ARI) is a global health problem that significantly contributes to high morbidity and mortality rates. The goal of this activity is to educate residents about preventing ARI, so that they have a good understanding of the disease and are able to take preventive measures independently. The program included information on ARI, simple inhalation therapy, and proper waste disposal. Prior to the health promotion on ARI prevention, 70% of residents had poor knowledge about the disease. After the activity, there was a significant increase in knowledge, with 90% of residents demonstrating a good level of understanding. This improvement indicates a positive shift in public awareness regarding ARI prevention. The activity successfully emphasized the importance of prevention efforts for ARI, focusing on promoting Clean and Healthy Living Behaviors (PHBS). Educating the community about ARI prevention is crucial in reducing the incidence of the disease. Regular health promotion activities, particularly those targeting community participation and practical steps for prevention, are vital for enhancing public health and preventing ARI, which remains a major cause of illness and death worldwide. The results highlight the effectiveness of health education in raising awareness and improving knowledge on preventing ARI.